Relationship between ankle mobility, elastic strength, and rate of force development in the two karate disciplines: Kata and kumite - Giardullo, G.; Di Lascio, G.; Ceruso, R.; Manzi, V.; Raiola, G. (Sci, 2025)
Karate is divided into two disciplines, Kata (forms) and Kumite (sparring), both of which are strongly influenced by the function of the tibiotarsal joint. However, the performance model differences between the two have not yet been thoroughly explored. The aim of this study is to evaluate the differences in ankle range of motion between Kata and Kumite, investigating the correlations between joint mobility, elastic strength, and Rate of Force Development (RFD). The sample consisted of 36 athletes, of male sex, evenly split between the two disciplines, who underwent a specific training protocol for three months. Three tests were administered: Weight Bearing Lunge, Counter Movement Jump, and Squat Jump. Data were analysed using Pearson`s correlation. In the Kata group, a moderate negative correlation emerged between ankle ROM and elastic strength (R = -0.521), and between ankle ROM and RFD (R = -0.570). In the Kumite group, the correlations were weakly negative: R = -0.261 for elastic strength and R = -0.257 for RFD. Greater ankle mobility, typical of Kata, appears to be associated with lower explosive capabilities, whereas more limited mobility in Kumite correlates with higher reactive strength and a faster rate of force development.